Recent Publications (Quarterly Journal of Economics, 1969)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 83, Issue 3, August 1969, Pages 529–531, https://doi.org/10.1093/qje/83.3.529 Published: 01 August 1969